Intelligent educational technologies in individual learning: a systematic literature review - Nurassyl Kerimbayev; Karlygash Adamova; Rustam Shadiev; Zehra Altinay (Smart Learning Environments)
Abstract This review was conducted in order to determine the specific role of intelligent technologies in the individual learning experience. The research work included consider articles published between 2014 and 2024, found in Web of Science, Scopus, and ERIC databases, and selected among 933 мarticles on the topic. Materials were checked for compliance with the criteria for headings, annotations and full texts and then further analyzed. The research study includes 38 review articles that were selected based on a rigorous evaluation and selection process in accordance with the PRISMA methodology and the AMSTAR2 critical assessment strategy. As a result of the analysis, it was found that the scope of application of intelligent technologies in individual education in research is diverse, and the results of articles on this topic are heterogeneous. The article identifies aspects of the effective use of intelligent technologies in education, emerging difficulties and limitations, as well as provides examples of successful implementation in various educational institutions. Although there are advantages to using smart technologies in education in general, we should not ignore what needs to be considered. On this point, the article presents the difficulties that arise when using intelligent technologies in education, and ways to prevent them.